Repulsive guidance molecule-A (RGM-A) inhibits leukocyte migration and mitigates inflammation - Mirakaj, Valbona; Brown, Sebastian; Laucher, Stefanie; Steinl, Carolin; Klein, Gerd; Köhler, David; Skutella, Thomas; Meisel, Christian; Brommer, Benedikt; Rosenberger, Peter; Schwab, Jan M. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Directed cell migration is a prerequisite not only for the development of the central nervous system, but also for topically restricted, appropriate immune responses. This is crucial for host defense and immune surveillance. Attracting environmental cues guiding leukocyte cell traffic are likely to be complemented by repulsive cues, which actively abolish cell migration. One such a paradigm exists in the developing nervous system, where neuronal migration and axonal path finding is balanced by chemoattractive and chemorepulsive cues, such as the neuronal repulsive guidance molecule-A (RGM-A). As expressed at the inflammatory site, the role of RGM-A within the immune response remains unclear. Here we report that RGM-A (i) is expressed by epithelium and leukocytes (granulocytes, monocytes, and T/B lymphocytes); (ii) inhibits leukocyte migration by contact repulsion and chemorepulsion, depending on dosage, through its receptor neogenin; and (iii) suppresses the inflammatory response in a model of zymosan-A–induced peritonitis. Systemic application of RGM-A attenuates the humoral proinflammatory response (TNF-α, IL-6, and macrophage inflammatory protein 1α), infiltration of inflammatory cell traffic, and edema formation. In contrast, the demonstrated anti-inflammatory effect of RGM-A is absent in mice homozygous for a gene trap mutation in the neo1 locus (encoding neogenin). Thus, our results suggest that RGM-A is a unique endogenous inhibitor of leukocyte chemotaxis that limits inflammatory leukocyte traffic and creates opportunities to better understand and treat pathologies caused by exacerbated or misdirected inflammatory responses.